Synthesis of Gd/N co-doped ZnO for enhanced UV-vis and direct solar-light-driven photocatalytic degradation. Issue 17 (10th March 2021) - Alanazi, Hamdah S.; Ahmad, Naushad; Alharthi, Fahad A.
Abstract : The construction of a UV-Vis and direct sunlight functioning photocatalyst is a puzzling task for organic pollutant removal. Abstract : The construction of a UV-Vis and direct sunlight functioning photocatalyst is a puzzling task for organic pollutant removal. Herein, we have fabricated Gd/N co-doped ZnO nanoparticles for the first-time using a simple co-precipitation method for photocatalytic degradation application. The heteroatom doping enhances the light absorption ability and acts as a photo-induced electron–hole separator by creating a trap state. Co-doped ZnO shows comparatively high photocatalytic degradation efficiency of about 87% and 93% under UV-Vis and direct solar light respectively. Moreover, the prepared photocatalyst exhibits excellent stability for the recycling process. Hence, we believe that this heteroatom co-doped ZnO photocatalyst is an auspicious material for the photocatalytic organic pollutant degradation reaction.